The pharmacophylogenetic relationships of two edible medicinal plants in the genus Artemisia - Cui, Zhanhu; Li, Siqi; Chang, Jiayin; Zang, Erhuan; Liu, Qian; Zhou, Baochang; Li, Chao; Li, Mengzhi; Huang, Xianzhang; Zhang, Zhongyi; Li, Minhui (Frontiers in Plant Science, 2022)
Artemisia argyi and Artemisia indica are edible medicinal plants belonging to the genus Artemisia in the Asteraceae. There are many similarities in their morphology, traditional curative effect, and modern pharmacological treatment. In this study, we built distribution maps of A. argyi and A. indica in China and a phylogenetic tree of common medicinal plants in Asteraceae. Then, we verified the chemical composition changes of A. argyi and A. indica via their metabolome. Traditional efficacy and modern pharmacological action were verified by network pharmacology and in vitro using RAW264.7 cells. The results showed that A. argyi and A. indica are widely distributed in China, and they shared pharmaphylogeny, which provides theoretical support for the mixed use of A. argyi and A. indica in most regions of China. Furthermore, there were both similarities and differences in volatile oil and flavonoid composition between A. argyi and A. indica. The network pharmacology results showed that A. argyi and A. indica had 23 common active compounds and that both had pharmacological effects on chronic gastritis. Molecular docking analyses showed that quercetin, luteolin, and kaempferol have strong binding affinities with the target proteins JUN, TP53, AKT1, MAPK3, TNF, MAPK, and IL6. The cell experiment results further demonstrated that A. argyi and A. indica treat chronic gastritis via the NOD-like receptor pathway. Based on the theory of pharmaphylogeny, this study explored the pharmaphylogeny between A. argyi and A. indica from various perspectives to provide a basis for the substitution of A. argyi and A. indica.